FORMULATION AND EVALUATION OF TINOSPORA CORDIFOLLA COUGH SYRUP CONTAINING GULVEL, TULSI, TURMERIC, HONEY AND GINGER. - Shendage Vaishnavi Sharad,; Gange Jay Nandkishor,; Purane Aditya Kalyaan,; Pawar Snehal Haushiram,; Masal Sakshi Sandip,; Panasare Vikram Jaysingh,; Dr.Kopnar Vishal Pandit,; Dr. Khedkar Amol Navnath, (The Bioscan, 2026)
Herbal medicines are widely used due to their natural origin, safety, affordability, and therapeutic benefits. Among medicinal plants, Tinospora cordifolia (Gilo) is well known for its immunomodulatory, anti-inflammatory, antimicrobial, antioxidant, and antipyretic properties. Traditionally, it has been used for the management of cough, fever, respiratory disorders, and immune-related conditions. The present study aimed to formulate and evaluate a herbal cough syrup containing Tinospora cordifolia as the main active ingredient. Honey was incorporated as a natural sweetening and soothing agent, while methyl paraben served as a preservative. Purified water was used as the vehicle. The formulation process involved extraction of active constituents, filtration, blending of ingredients in appropriate proportions, volume adjustment, and homogenization to obtain a uniform syrup. The prepared syrup was evaluated for physicochemical parameters such as appearance, color, odor, taste, pH, viscosity, density, specific gravity, clarity, and sedimentation behavior. Stability and basic quality control assessments were also performed to ensure product safety and effectiveness. The formulation exhibited acceptable organoleptic characteristics, suitable pH and viscosity, good clarity, and satisfactory physical stability. These results indicate that the developed Tinospora cordifolia herbal cough syrup possesses desirable pharmaceutical properties and may serve as a promising natural alternative for cough relief and respiratory support. Further pharmacological and clinical studies are required to confirm its therapeutic efficacy and long-term safety.